Freshwater fishes of Iraq: a revised and updated annotated checklist—2023 - Çiçek, Erdoğan; Jawad, Laith; Eagderi, Soheil; Esmaeili, Hamid Reza; Mouludi-Saleh, Atta; Sungur, Sevil; Fricke, Ronald (Zootaxa, 2023)
The current status of the freshwater fishes of Iraq is revised, and an updated checklist is presented. The confirmed freshwater fishes of Iraq comprise 98 species belonging to 16 orders, 28 families, and 56 genera. Among these, 21 species (21.4%) are alien, and three species (3.0%) are considered endemic to Iraq. The orders with the largest numbers of species in the ichthyofauna of Iraq are Cypriniformes (57 species), followed by Siluriformes (12 species), Mugiliformes and Cyprinodontiformes (six species in each), Acanthuriformes and Cichliformes (three species in each), Centrarchiformes and Gobiiformes (two species in each), and the others represent only one species. At the family level, the Cyprinidae have the greatest number of species (28; 28.3% of the total species), followed by Nemacheilidae (16 species), Leuciscidae (eight species), Mugilidae (six species), Sisoridae (five species), and Xenocyprididae (four species in each). A total of 20 species that have been previously reported from Iraq have been excluded from the checklist. According to IUCN Red List criteria, among 77 naturally distributed species (alien species not included), 10 species (13.0%) are categorized as threatened extinctions, with three (3.9%) as CR, one (1.3%) as EN, and six (7.8%) as VU. A total of 38 taxa were assessed (49.4%) as LC, 27 species were not assigned NE (35.1%), and two species (2.0%) were classified as DD, i.e., with insufficient knowledge.